ОБ ОДНОМ МЕТОДЕ РАСЧЕТА НАТЯЖЕНИЯ ПЕРЕДАТОЧНОГО МЕХАНИЗМА С РАСТЯЖИМЫМ РЕМНЕМ (Scientific journal of the Fergana State University, 2023)
When rotating, the transmission mechanisms are subjected to high loads, which requires taking into account the stretching of the belt material. The article presents the formulation and solution of the problem of rotation of a transmission belt with two internal and two external pulleys rotating in a stationary mode at a given speed.